Pengawasan dalam Perspektif Islam dan Manajemen - Sugiharto, Bambang; Syaifullah, Muhammad (ILTIZAM Journal of Shariah Economics Research, 2023)
The reason for this study is to look at oversight according to an Islamic point of view and the sort of management wanted in Islam. In practice, there are a lot of irregularities in both government and non-government organizations that result in a lot of losses, both financial and non-financial. This is why supervision is so important. However, the majority of those responsible are Muslims. Utilizing composed information, this study utilizes a subjective methodology in view of writing studies. by investigating and utilizing the information contained in the Koran, Sunnah, assessments of researchers, reference books, and logical diaries that are distributed electronically, utilizing the methodology of content examination and maudhui understanding. According to the findings of this study, supervision from an Islamic perspective is: supervision that is already in place in humans, such as the belief that Allah will always watch over and punish humans for their actions; and supervision for both individuals and groups in the form of amar ma’ruf nahi munkar. A form of Islamic supervision that is carried out by leaders and members of communities or organizations is individual piety derived from monotheism and faith in Allah SWT. Systems and technology are used to implement and enforce sharia-compliant rules